The intervention effect of structured martial arts games on behavioral impairments and motor functions in children with autism spectrum disorder - Fu, Xuexiang; Shi, Peng (Frontiers in Psychology, 2025)
ObjectiveThis study aims to explore the intervention effect of an intervention program based on structured martial arts games on behavioral and motor function disorders in children with autism spectrum disorder (ASD), and to provide a novel and effective intervention strategy for ASD children to enhance their rehabilitation outcomes.MethodsA randomized controlled trial design was adopted. Fifty-six ASD children were selected from a special education school and randomly divided into an experimental group (28 people) and a control group (28 people). The experimental group received a 24-week structured martial arts game intervention, 3 times a week, 60 min each time; the control group received traditional rehabilitation training. The autism treatment evaluation checklist, autism behavior checklist, and gross motor function measure were used to evaluate the relevant indicators of the two groups of children before and after the intervention, and SPSS 26.0 software was used for statistical analysis.ResultsAfter the intervention, the improvement of the experimental group in language ability, social communication ability, perceptual ability, health behavior and total score was significantly better than that of the control group (p < 0.05). The experimental group was significantly better than the control group in sensory ability, social ability, motor ability, language ability, self-care ability and total score (p < 0.05). The improvement of the experimental group in lying and rolling, sitting, crawling and kneeling, standing, walking, running and jumping, and total score was significantly higher than that of the control group (p < 0.05).ConclusionThe structured martial arts game intervention can effectively improve the behavioral and motor disorders of ASD children. This intervention method is both interesting and structured, and can be used as a new approach for the rehabilitation of ASD children. It is recommended to incorporate it into the regular curricula of special education schools and rehabilitation institutions.